Comportamiento agronómico de cuatro hortalizas de hoja con tres abonos orgánicos en la hacienda Tecnilandia – Quevedo. - Zaráuz Flores, Jorge Eduardo (2013)
The present investigation realized in the Estate Tecnilandia located in kilómetro/11 Route to The Junction straight margin; belonging to the Canton Quevedo, province of The Rivers. His geographical location is of 01th 6 ' of latitude South and of 79th 29 ' of length West, with an altitude of 100 (msnm), the investigation had a duration of 180 days. The treatments under study were: H1 Celery; H2 Coriander; H3 Parsley; H4 Lettuce; T0 Witness; T1 Humus of worm; T2 Water hyacinth (Jacinto de agua) and T3 Water hyacinth + Humus of worm. (DBCA) was in use a Design of Complete Blocks at random in three more repetitions a witness. To determine the statistical difference there was in use the test of Tukey's multiple ranges to 5 % of probability. The results were: In height of plants to 60 days there is had that inside the group of humus of worm he presented the major development with an average of 49.80 cm for the celery; 50.27 cm for the coriander and 45.33 cm in the parsley, not this way in the lettuce since the treatment with Jacinto de agua obtained the major average with 22.47 cm. Regarding the production and yield of the celery, it appreciates that the treatment Celery + Humus of worm reached the major diameter of stem with 6.07 cm; in numbers of branches with 11.93 branches; I weigh 1806.50 g and in yield with 18.07 t there is 1. In the weight of the coriander, the treatment Coriander + humus + Jacinto de agua brought the major average with 630 g as the yield for hectare with 6.16 t/ha, in number of branches the same treatment brought the best average with 28.07 branches. Weight and performance of the parsley, the treatment with Vermicompost + Jacinto de agua resulted with the best average with 776.83 g and 7.77 tha-1. Lettuce treatment + Vermicompost showed best results in diameter of stem with 3.04 cm; weight with 472.33 g and performance with 4.73 t ha-1.............................